The Bidayuh Mountain Framework: An Indigenous Model of Reversing Language Shift (RLS) - Burkhardt, Jey Lingam *; Noeb, Jonas; Ridu, Robert Sulis (Dayak Bidayuh National Association, 2017)
In his ground-breaking work Fishman (1991) introduced and expounded the notion of Reversing Language Shift (RLS) using a "Richter Scale" typology, which became known as Fishman’s GIDS (Graded Intergenerational Disruption Scale). The use of “Richter Scale” provided metaphors to facilitate discussions of the language revitalization process that is useful in many situations. However, as it is, the metaphor is not always easily understood and applied by ethnic minority speakers engaged in their own language revitalization efforts. In our efforts to understand in a concrete way what was sought by Fishman’s typology, we have developed an indigenous model. The “Bidayuh Mountain Framework”, which provides a straightforward account of the relationship between life and language in the Bidayuh context, is the model that was developed to help the Bidayuh people understand what is involved in “reversing language shift” and promoting the development and revitalisation of their language. The presenters will describe the model, its process of development and the way it is being used. They will also look at the potential for expanding the model so that it can be used to assist language revitalisation efforts in other minority language communities.